NEW DATA ON QUATERNARY PROCESSES OF UNDERWATER SLUMPING ON THE WESTERN SLOPE OF THE DERBENT BASIN (CASPIAN SEA) - Verzhbitskii V.E.; Levchenko O.V.; Lobkovskii L.I. (My University, 2007)
The structure of the sedimentary sequence of the Caspian Sea has been scrutinized by geological and geophysical methods, including seismic profiling. It is mostly concerned with relatively deep Lower Cenozoic–Upper Mesozoic horizons with the potential presence of hydrocarbon traps. However, the uppermost sedimentary horizons of the Quaternary age are poorly studied, because it is rather difficult to sample these slightly lithified sediments during exploration drilling. For example, the published data on the lithology and stratigraphy of marine sediments on the western slope of the middle Caspian region near the Dagestan coast are limited by geological columns only up to some meters. The same situation is true for the extent of study of the sedimentary sequence structure by continuous seismic profiling (CSP). The CSP investigation was mainly carried out in the 1970s and 1980s using low-resolution profiling systems. The superhighresolution CSP investigation was carried out for the first time in the Yalama–Samur structure with petroleum potential within the framework of the Federal Program “World Ocean” (Subprogram 0008 “Comprehensive Studies of Processes, Characteristics, and Resources of the Caspian Sea”) and a geological–engineering survey carried out for the Lukoil Company during Cruise 19 of the R/V Rift on the western slope of the Derbent basin in the autumn of 2004.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная